2016
DOI: 10.3390/bioengineering3030017
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Characterization of Chitosan Enzymolysis by Pepsin

Abstract: Pepsin was used to effectively degrade chitosan in order to make it more useful in biotechnological applications. The optimal conditions of enzymolysis were investigated on the basis of the response surface methodology (RSM). The structure of the degraded product was characterized by degree of depolymerization (DD), viscosity, molecular weight, FTIR, UV-VIS, SEM and polydispersity index analyses. The mechanism of chitosan degradation was correlated with cleavage of the glycosidic bond, whereby the chain of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…According to this figure, after an interval of 3 h, chitosanase has the highest capacity of chitosan hydrolysis, followed by pepsin, then α-amylase. The optimum enzyme concentration for pepsin is 110 mg/L, which equals a 1.1% ( w/w ) enzyme-substrate ratio, as reported by T. Roncal et al (2007) [25,26]. According our study, the optimum enzyme concentration was 5 U for chitosanase and 80 U/g for α-amylase, similar to previous reports.…”
Section: Resultssupporting
confidence: 89%
“…According to this figure, after an interval of 3 h, chitosanase has the highest capacity of chitosan hydrolysis, followed by pepsin, then α-amylase. The optimum enzyme concentration for pepsin is 110 mg/L, which equals a 1.1% ( w/w ) enzyme-substrate ratio, as reported by T. Roncal et al (2007) [25,26]. According our study, the optimum enzyme concentration was 5 U for chitosanase and 80 U/g for α-amylase, similar to previous reports.…”
Section: Resultssupporting
confidence: 89%
“…It was suggested that acidic condition and long shaking (1 hr) of mixture increased the solubility of chitosan and enhanced the interactions of chitosan with oil droplets. Additionally, pepsin might cause the partial hydrolysis of chitosan, resulting in the lower MW chitosan (Gohi, Zeng, & Pan, ). Low MW chitosan could migrate into interface rapidly and stabilize emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…Physical processes include depolymerization with sonication [26], electromagnetic irradiation, gamma irradiation [60,61], microwave irradiation, or a thermal procedure [62]. Finally, enzymatic processes use specific enzymes like chitinase [63] and chitosanase [64], but also non-specific enzymes, such as pepsin [65], cellulase [66], lipase, pronase, protease [67], lysozyme, papaïn, glucanase, hemicellulase, or pectinase. However, the main issues of enzymatic depolymerization are probably the cost of making it redhibitory for bulk use in commercial applications and the relative slowness of reactions.…”
Section: Chitooligosaccharide (Cos) and Low Molecular Weight (Lmw) Chmentioning
confidence: 99%